Formation of a religious landscape : Shi'i higher learning in Safavid Iran - Moazzen, Maryam. (Islamic History and Civilization, 2018)
In Formation of a Religious Landscape: Shi'i Higher Learning in Safavid Iran , Maryam Moazzen offers the first systematic examination of Shi'i educational institution and practices by exploring the ways in which religious knowledge was produced, authenticated, and transmitted in the second half of Safavid rule (1588-1722). By analyzing the deeds of endowment of the Madrasa-yi Sulṭānī and other mosque-madrasas built by the Safavid elite, this study sheds light on the organizing mechanisms and structures utilized by such educational foundations. Based on the large number of ijazās and other primary sources including waqfiyyas , biographical dictionaries and autobiographies, this study also reconstructs the Safavid madrasas' curriculum and describes the pedagogical methods used to transmit religious knowledge as well as issues that faced Shi'i higher learning in early modern times.